2004
DOI: 10.1093/ajcn/79.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and obesity-related metabolic disorders in Taiwanese and US whites and blacks: implications for definitions of overweight and obesity for Asians

Abstract: These data suggest a possible need to set lower BMI cutoffs for Asians, but where to draw the line is a complex issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
234
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(249 citation statements)
references
References 25 publications
14
234
0
1
Order By: Relevance
“…The data collected on smoking, physical activity, and diet from the self‐administered questionnaires may be subject to recall bias. Future modifications of the LS7 metrics could make BMI specific for each racial/ethnic group because some studies have demonstrated that Asians are at a higher risk of weight‐related diseases, such as CVDs, at lower BMIs 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…The data collected on smoking, physical activity, and diet from the self‐administered questionnaires may be subject to recall bias. Future modifications of the LS7 metrics could make BMI specific for each racial/ethnic group because some studies have demonstrated that Asians are at a higher risk of weight‐related diseases, such as CVDs, at lower BMIs 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained on several accounts. It has been suggested that 60% of FRAP activity is contributed by uric acid and hyperuricemia as part of the metabolic syndrome [2,[42][43][44] may be responsible for higher FRAP in the NAFLD group. The increase in FRAP levels may occur as a compensatory phenomenon in NA-FLD patients to protect against OS.…”
Section: Discussionmentioning
confidence: 99%
“…Because the metabolic risks at a given BMI value are greater in Asians than Caucasians, it is generally accepted that BMI values used for defining overweight and obesity in Asians should be lower than those used for Caucasians (33,34). Therefore, studies investigating the impact of obesity on balance and mobility outcomes in Asian patients post-TKR should use a BMI cutoff value of 27 kg/m 2 for defining obesity rather than a value of 30 kg/m 2 , which is commonly used for Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI can be used to distinguish between overweight and obese individuals within a single ethnic group (31). However, BMI cutoff values should be lowered when defining overweight and obesity in Asians (32)(33)(34). Thus, for the Asian patients included in the current study, we used BMI values of 18.5-23.9 kg/m 2 , 24.0-26.9 kg/m 2 , 27.0-29.9 kg/m 2 , 30-34.9 kg/m 2 , and .35 kg/m 2 to define normal weight, overweight, class I obesity, class II obesity, and class III obesity, respectively.…”
Section: Methodsmentioning
confidence: 99%